∆*-Locally Continuous Functions and ∆*-Locally Irresolute Maps in Topological Spaces - Meena, K.; Sivakamasundari, K. (International Journal of Engineering and Technology, 2018)
The objective of the paper is to introduce a new types of continuous maps and irresolute functions called ∆*-locally continuous functions and ∆*-irresolute maps in topological spaces. The comparative study between these functions with other existing maps is discussed in this paper. Some significant results are also proved as an application of new spaces namely, ∆*-submaximal space and  –space. Further the characteristics of these maps under composition maps are exhibited.